Numerical Study of a Wind Turbine Blade Modification Using 30° Angle Winglet on Clark Y Foil - Arini, Nu Rhahida; Gilang Muhammad; Joke Pratilastiarso; Setyo Nugroho (EMITTER International Journal of Engineering Technology, 2022)
The depletion of fossil fuels and the worsening environment motivate engineers and researchers to explore renewable energy resources. One of the promising renewable energy is wind energy. The wind turbine extracts wind energy to generate electricity. This study aims to modify a wind turbine blade using Clark Y foil to improve the lift force. The modification is employed by forming a winglet profile with a 30° angle on the foils tip. The result shows that the 30° winglet enlarges the lift coefficient to 1.3253 from 1.2795 of the original blade lift coefficient.